WIZERUNKI ŚWIĘTYCH CYRYLA I METODEGO – NUMIZMATYCZNA IDEOLOGIZACJA PRZESZŁOŚCI - JÓŹWIAK, WOJCIECH (Slavia Occidentalis, 2020)
Great work of “the Solun Brothers” – Saints Cyril and Methodius – undoubtedly played important part in the creation of national identity and national awarenessof many Slavic nations. Considering the importance of the legacy of Cyril and Methodius, it seems surprising how rarely their images were used on national coins which are among the most common and most important symbols of independent nations. The only countries to have paid tribute to “the Solun Brothers” in the process of creating their national identities were Slovakia, Czechia, Bulgaria and Macedonia. They did it by placing the saints in cultural, political and ideological contexts on collectors’ items and regular currency.